Environmental tobacco smoke in homes, motor vehicles and licensed premises: community attitudes and practices - Raoul A. Walsh; Flora Tzelepis; Christine L. Paul; Jeanie McKenzie (Elsevier, 2002)
Abstract Objective: To assess community knowledge, attitudes and practices in relation to environmental tobacco smoke (ETS) especially in homes, private motor vehicles and licensed premises, and to document levels of support for further government legislation. Methods: 656 persons aged 18 years and over, a sub‐sample in a computer‐assisted telephone survey of 2,087 randomly selected respondents across NSW, answered 12 ETS‐specific questions The whole sample was asked demographic, smoking status and household membership questions. The overall response rate was 61.4% (consent rate 75.4%). Results: Overall, 32.8% (95% CI 27.8-37.8) of children aged 0-4 years in the households surveyed were reported to live with at least one smoker. Agreement about ETS hazards was lowest in relation to child ear problems (31.2%) and sudden infant death syndrome (50.6%). Complete bans on smoking were reported in 69.9% of homes and 77.1% of private motor vehicles The percentages favouring total bans in homes (p<0.001) and private motor vehicles (p<0.001) were significantly lower among smokers than non‐smokers. Overall, 55.8% supported legislation to ban smoking in private vehicles carrying children. The majority support restrictions on smoking in non‐eating areas of licensed clubs (88.7%) and hotels (84.8%). Overall, the data indicate a ban on smoking in licensed premises is likely to increase business. Conclusion: Smoking is banned in most NSW homes and private motor vehicles Acceptance of ETS risks is high but there are important knowledge gaps. Considerable support exists for further government regulation of ETS. Media campaigns are likely to reinforce a public environment already receptive of the need for more government ETS restrictions.